Of oncogenes and open science: an interview with Harold Varmus - Harold Varmus (The Company of Biologists, 2019)
Harold Varmus has made pioneering contributions to our understanding of cancer as a genetic disease. The discovery of the cellular origin of retroviral oncogenes earned him and his long-term collaborator, Michael Bishop, the Lasker Prize for Basic Medical Sciences in 1982 and the Nobel Prize in Physiology and Medicine in 1989. Throughout his career, Varmus has held several leadership roles that shaped science policy in the US and worldwide, and he has been an outspoken advocate for open science. In this interview, he talks (among other things) about the factors that shaped his early career choices, the thrill of scientific discovery, and the importance of including diverse populations in genomic studies of cancer and other diseases.